Ru-Doped Wells–Dawson Polyoxometalate as Efficient Catalyst for Glycerol Hydrogenolysis to Propanediols - Modvig, Amalie (Materials (Basel), 2019)
A Ru-doped phospho-tungstic Wells–Dawson polyoxometalate (POM) was successfully applied as homogeneous catalyst for glycerol hydrogenolysis in aqueous media. The synthesized compound showed superior catalytic activity compared to classical homogeneous/heterogeneous Ru catalysts like RuCl(3) and Ru/C under identical reaction conditions, whereas the analogous POM doped with Pd or Pt proved far less activity. Detailed characterization of the POMs was performed using (31)P-NMR to identify characteristic phosphorous peaks of the heteroatoms, infrared spectroscopy (ATR-FTIR) to confirm characteristic P-O and W-O-W vibrations, powder XRD for comparison of crystal structures, and X-ray fluorescence (XRF) and inductive-coupled plasma (ICP) analysis to determine elemental composition. Variation of the reaction parameters for the best performing Ru-doped POM catalyst showed that substrate concentration played an important role for both product selectivity and conversion. Moreover, medium hydrogen pressure and high stirring speed were key factors to obtain highly selective conversion of glycerol to 1,2-propanediol.